The role of immune microenvironment in small-cell lung cancer: Distribution of PD-L1 expression and prognostic role of FOXP3-positive tumour infiltrating lymphocytes. (September 2018) - Bonanno, L.; Pavan, A.; Dieci, M.V.; Di Liso, E.; Schiavon, M.; Comacchio, G.; Attili, I.; Pasello, G.; Calabrese, F.; Rea, F.; Favaretto, A.; Rugge, M.; et al.
Abstract: Introduction: The prognosis of small-cell lung cancer (SCLC) is dismal and new effective therapies are needed. Immunotherapy looks promising, but no molecular predictive markers are currently available, and data on immune microenvironment are very limited. Methods: We retrospectively analysed 104 SCLC cases. Immunohistochemistry evaluation of PD-L1 was performed both on tumour cells (TCs) and on tumour-infiltrating immune cells (TIICs) by using anti-PD-L1 22C3 antibody (DAKO) and categorised by using 1% as cut-off point. Tumour-infiltrating lymphocytes (TILs) were characterised by using anti-CD8 and anti-FOXP3 antibodies. Semi-quantitative score was used and categorised as positive versus negative/low. The relation of molecular markers with prognosis and with clinical variables was evaluated. Results: The analysis included 66 stage I–III patients (48 surgically resected, 18 treated with radical-intent chemoradiotherapy) and 38 metastatic cases. In the overall study population, PD-L1 was expressed on TCs and TIICs in 25% and 40% of cases, respectively. The proportion of PD-L1-positive cases was significantly higher in stage I–III versus metastatic patients (32% versus 13%, p: 0.034 for TCs; 51.5% versus 21% for TIICs, p: 0.002). CD8- and FOXP3-positive TILs were present in 59% and 72% of samples, respectively. The presence of FOXP3-TILs was associated with improved prognosis among non-metastatic patients, with a hazard ratio for survival of 0.32 (95% confidence interval [CI]: 0.16–0.7, p: 0.006) for univariate analysis, and 0.37 (95% CI: 0.17–0.81, p: 0.013) for multivariate analysis. Conclusions: Immune contexture of SCLC may differ according to stage. The presence of FOXP3-positive TILs is a potential prognostic marker for stage I–III SCLCs and warrants further investigation. Highlights: The study depicts distribution of PD-L1 expression in small-cell lung cancer (SCLC) according to stage. The study characterises tumour-infiltrating lymphocytes (TILs) in SCLC. Independent positive prognostic impact of FOXP3-TILs is shown in stage I–III SCLCs.